2018
DOI: 10.1126/sciadv.aao1761
|View full text |Cite
|
Sign up to set email alerts
|

High-capacity aqueous zinc batteries using sustainable quinone electrodes

Abstract: Sustainable and ubiquitous organic quinone cathodes contribute to high-capacity and safe rechargeable zinc batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
589
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 835 publications
(610 citation statements)
references
References 57 publications
(109 reference statements)
18
589
2
1
Order By: Relevance
“…[173] The order of average V platform from low to high was 9,10-AQ, 9,10-PQ, 1,4-NQ, 1,2-NQ, and C4Q. [173] The order of average V platform from low to high was 9,10-AQ, 9,10-PQ, 1,4-NQ, 1,2-NQ, and C4Q.…”
Section: Neutral Aqueous Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…[173] The order of average V platform from low to high was 9,10-AQ, 9,10-PQ, 1,4-NQ, 1,2-NQ, and C4Q. [173] The order of average V platform from low to high was 9,10-AQ, 9,10-PQ, 1,4-NQ, 1,2-NQ, and C4Q.…”
Section: Neutral Aqueous Solutionmentioning
confidence: 99%
“…Although aqueous solution batteries are still in their infancy, various cationic batteries in an aqueous electrolyte with nucleophilic addition reaction of the carbonyl are discussed, such as those of H + , [165] NH 4 + , [65] Li + , [166,167] K + , [168,169] Na + , [170][171][172] Mg 2+ , [62] Zn 2+ , [173][174][175] and Ca 2+ . Improving the conductivity and binding in the active material, and the selection of a solid electrolyte and gel electrolyte, could alleviate the side effects.…”
Section: Electrochemical Behavior Of Accs In Aqueous Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic electrodes materials are also feasible for aqueous AZBs. Very recently, Chen and co‐workers reported the application of quinone electrodes in aqueous zinc battery. The results indicated that the quinone compounds with carbonyls in ortho ‐position (1,2‐naphthoquinone (1,2‐NQ) and 9,10‐phenanthrenequinone (9,10‐PQ)) generally show lower capacity and larger polarization than those with carbonyls in para ‐position (1,4‐naphthoquinone (1,4‐NQ), 9,10‐anthraquinone (9,10‐AQ), and calix[4]quinone (C4Q)) due to the larger steric hindrance.…”
Section: Aqueous Batteries Using Multivalent Ions (Zn2+ Mg2+ Ca2+ mentioning
confidence: 99%
“…The results indicated that the quinone compounds with carbonyls in ortho ‐position (1,2‐naphthoquinone (1,2‐NQ) and 9,10‐phenanthrenequinone (9,10‐PQ)) generally show lower capacity and larger polarization than those with carbonyls in para ‐position (1,4‐naphthoquinone (1,4‐NQ), 9,10‐anthraquinone (9,10‐AQ), and calix[4]quinone (C4Q)) due to the larger steric hindrance. And the carbonyls with more negative electrostatic potential (ESP) prefer to be active sites for Zn‐ion storage ( Figure ) …”
Section: Aqueous Batteries Using Multivalent Ions (Zn2+ Mg2+ Ca2+ mentioning
confidence: 99%